Chemical Composition and Fatty Acid Profile of Some Indonesian Sea Cucumbers - Yusro Nuri Fawzya; Hedi Indra Januar; Rini Susilowati; Ekowati Chasanah (Research and Development Center for Marine and Fisheries Product Processing and Biotechnol, 2015)
Indonesia has a great sea cucumber resource which is useful as functional food. Even though much information about the biopotency of sea cucumbers have been published, however, studies on nutrition value of Indonesian sea cucumbers are still beneficial due to the great diversity and uniqueness of each species. The present work was intended to obtain information about chemical composition and fatty acid profile of 4 (four) types of sea cucumbers which are frequently found in Halmahera water, North Maluku (Molucca), one of sea cucumbers producing area in Indonesia. The samples coded as H-03, H-04, H-05 and H-10, were identified as Bohadschia argus, Holothuria fuscogilva, Thelenota ananas, and Actinophyga lecanora. All sea cucumbers showed high protein content, more than 60% (drybase/db), except for T. ananas which had the lowest protein content (48.26% db). As for fats, T. ananas showed the highest amount (2.35%db) with dominated saturated fatty acids (SFA). On the other side, A. lecanora showed higher value of PUFA compared to SFA and MUFA. Palmitic acid (C16:0) was the most abundant SFA in the most samples with the amount of 0.49–4.9 mg/g sample. Among PUFA, eicosapentaenoic acid/EPA (C20:5n3) was detected, and eicosatrienoic acid (C20:3n6) was relatively higher than the others. The ratio of w6/w3 fatty acid was 1.2–3.2 showing that total w6 fatty acid was higher than total w3 fatty acid. However, this value is safe enough to protect against chronic and degenerative diseases.